Psikoedukasi Kontrol Diri sebagai Bentuk Relapse Prevention pada Warga Binaan Kasus Narkoba - Nastiti, Dwi; Affandi, Ghozali Rusyid; Fahmawati, Zaki Nur; Mitasari, Riska Dwi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Self-Control Psychoeducation as a Form of Relapse Prevention for Residents Involved in Drug Cases. This research was conducted based on the phenomenon of recovery and relapse episodes in inmates involved in drug cases. The occurrence of a relapse hinders the achievement of one of the SDGs goals, namely ensuring a healthy life and improving the welfare of the population at all ages. Therefore, this research needs to be carried out. According to Marlat and Gordon. The factor that influences the tendency to relapse is weak self-control (Wulandari et al., 2020). One way that can be done to prevent relapse is by providing psychoeducation related to self-control. The aim of this research is to apply self-control psychoeducation as a form of relapse prevention for inmates involved in drug cases. This research uses the Pretest-Posttest Design experimental method. The participants in this research were 29 inmates with drug cases who returned to prison with the same case (relapse) who were selected based on non-probability sampling. Measurement of the level of understanding of self-control using the Self-Control Scale. Data analysis used t-test analysis on pre-test and post-test results with the help of JASP version 17 The results of the analysis show that of the 29 inmates who took part in psychoeducation, there were 18 inmates whose understanding of self-control increased, 7 remained the same and 4 decreased. This research hopes that inmates will be able to maximize their self-control so that they will not relapse when they leave prison, and can focus more on getting a decent life.